Pengelasan Gas Tungsten Arc Welding (GTAW) dan Underwater Welding (UW) pada Perbaikan Propeller berbahan Kuningan - Andre Anggriawan Jaisi Djailani Putra; Dwisetiono Dwisetiono (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Over time, marine building technology has experienced very significant developments and there are several variations of improvements that can be made to suit needs and conditions. A ship's propeller is a ship component that often experiences collisions with hard objects floating in the water which can cause the blades of the propeller to experience damage such as bending, cracking or breaking. In this case, the propeller should be repaired immediately so as not to disrupt the smooth operation of the ship. Repairing broken propeller blades can be done using a welding process. Welding is a technique of joining metals by melting part of the parent metal and filler metal with or without additional metal and producing continuous metal. Underwater Welding is a welding process that occurs in wet conditions, meaning that the electrode and object are in direct contact with air, while Gas Tungsten Arc Welding (GTAW) is an electric arc welding process that uses an untreated electrode that does not melt. This research was conducted to analyze the welding measurement results of Gas Tungsten Arc Welding (GTAW) and Underwater Welding on brass materials. To support the analysis process, testing activities are carried out including tensile tests (tensile test), hardness tests (hardness test) and macrographic observations on the results of welding materials.